A Study on Finding the Factors, Hindering the use of digital wallets among youth in Developing Countries (Global Journal of Computer Science and Technology, 2021)
A digital wallet or eWallet is a mobile base software application that securely persists consumer s payment information and passwords for numerous payment methods By using an eWallet users can complete their transactions easily and quickly with technologies such as Quick Response QR and near-field communications NFC In the modern world people use digital wallets to engage in financial and non-financial activities using the internet It stores physical financial instruments digitally and provides high availability to convenience to the user Typically to facilitate high security to those financial assets in the digital wallet of the user and to maintain reliability and availability mobile application developing organizations follow different authorization mechanisms Problem prevailing in a developing country similar to Sri Lanka is the less use of digital wallets in day to day transactions The final outcome of the research will be to find the factors which affect the use of digital wallets in Sri Lankan students who study in western province universities
Keywords: eWallet; digital wallet; UTAUT-3; Unified theory of acceptance and use of technology 2013; 3; user adoption; behavioral intention